Drug resistance in Shigella dysenteriae, S flexneri and S boydii in England and Wales: increasing incidence of resistance to trimethoprim. Issue 6419 (10th March 1984) - Gross, R J; Threlfall, E J; Ward, L R; Rowe, B
Abstract : A total of 2753 strains of shigella belonging to subgroups A, B, and C that were isolated from patients in England and Wales during the period from 1979 to mid-1983 were studied. Of these, 1690 (61%) were from patients recently returned from abroad or in contact with recent travellers, and 760 (45%) of these affected travellers from the Indian subcontinent. The number of strains resistant to sulphonamides and streptomycin remained at a high level throughout (average 76% and 72% respectively). Resistance to tetracyclines, ampicillin, and chloramphenicol rose, reaching 63%, 51%, and 48%, respectively, in 1982. Strains resistant to trimethoprim were seen in substantial numbers for the first time and increased from 1.3% of all strains in 1979 to 9.9% in 1982 and 16.8% in the first half of 1983. The proportion of patients with recent foreign contact was notably smaller among those with strains resistant to trimethoprim than among those with strains sensitive to trimethoprim. The increase in resistance to trimethoprim might partly result from the use in Britain of compounds containing trimethoprim for the treatment of shigellosis.